1982
DOI: 10.1128/iai.36.2.484-491.1982
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone regulation of the effector function of malarial immunity during pregnancy

Abstract: In the experimental Plasmodium berghei mouse model, as in human malaria, reduced maternal responsiveness and even loss of immunity were observed during pregnancy. Loss of immunity in the second half of pregnancy occurred during a period of elevated plasma corticoid levels. Further analysis showed that plasma corticoid levels were significantly higher in immunodepressed mice than in mice that remained immune throughout pregnancy. Plasma corticosterone levels differed increasingly from those in mice with persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…Loss of immunity during pregnancy was related to increased levels of both total and free plasma corticosterone. Moreover, when the increase in plasma corticosterone in the mother was prevented by adrenalectomy before pregnancy, loss of immunity during pregnancy was drastically reduced (van Zon et al 1982). These results suggested that reduced immune reactivity during pregnancy causing loss of a pre-existing anti-malaria immunity was causally related to pregnancy-dependent changes in corticosterone levels.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Loss of immunity during pregnancy was related to increased levels of both total and free plasma corticosterone. Moreover, when the increase in plasma corticosterone in the mother was prevented by adrenalectomy before pregnancy, loss of immunity during pregnancy was drastically reduced (van Zon et al 1982). These results suggested that reduced immune reactivity during pregnancy causing loss of a pre-existing anti-malaria immunity was causally related to pregnancy-dependent changes in corticosterone levels.…”
Section: Discussionmentioning
confidence: 89%
“…Corticosterone in the minipump (25 pg/pl) resulted in a calculated release of 258 pg/24 h. Although this dose seems high in relation to the basal plasma level of 0.1 pg/ml plasma (van Zon et al 1982), it did not result in a detectable increase in the plasma corticosterone concentration during the 3 week period following implantation of the minipumps (results not shown).…”
Section: Effect Of Glucocorticoid Treatmentmentioning
confidence: 88%
See 2 more Smart Citations
“…As a matter of fact, several authors have referred to increased susceptibility to infection or the exacerbation of infectious diseases caused by bacteria (3,22), viruses (17,22,38), or protozoa (22,40) during pregnancy. In some experimental infections of mice, pregnancy is reported to result in impaired protection against some kinds of M. SANO ET AL viruses (4,10,13,14), Plasmodium berghei (43,44), and Listeria monocytogenes (19,25). L. monocytogenes is one of the bacteria which induce typical T cell-mediated immunity.…”
Section: Impairment Of T Cell-mediatedmentioning
confidence: 99%